2012
DOI: 10.1016/j.cub.2012.03.054
|View full text |Cite
|
Sign up to set email alerts
|

Attention Samples Stimuli Rhythmically

Abstract: Overt exploration or sampling behaviors, such as whisking, sniffing, and saccadic eye movements, are often characterized by a rhythm. In addition, the electrophysiologically recorded theta or alpha phase predicts global detection performance. These two observations raise the intriguing possibility that covert selective attention samples from multiple stimuli rhythmically. To investigate this possibility, we measured change detection performance on two simultaneously presented stimuli, after resetting attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

102
742
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 558 publications
(855 citation statements)
references
References 33 publications
102
742
11
Order By: Relevance
“…Evidence supporting this possibility in human studies shows that the phase of entrained or cross-modally reset cortical oscillations can have subtle effects on auditory perception (24,45,46), behavioral response times (26), and visual detection thresholds (23,40,47,48). Previous work has also shown both that the degree of multisensory perceptual binding is modulated by stimulus type (5), task (49), and prior experience (50), and that oscillatory entrainment adjusts as a function of selective attention to visual or auditory stimuli (51,52). Given this it seemed important to first investigate multisensory interactions in voice-sensitive cortex during a visual fixation task irrelevant to the specific face/voice stimuli, so as to minimize taskdependent influences.…”
Section: Discussionmentioning
confidence: 79%
“…Evidence supporting this possibility in human studies shows that the phase of entrained or cross-modally reset cortical oscillations can have subtle effects on auditory perception (24,45,46), behavioral response times (26), and visual detection thresholds (23,40,47,48). Previous work has also shown both that the degree of multisensory perceptual binding is modulated by stimulus type (5), task (49), and prior experience (50), and that oscillatory entrainment adjusts as a function of selective attention to visual or auditory stimuli (51,52). Given this it seemed important to first investigate multisensory interactions in voice-sensitive cortex during a visual fixation task irrelevant to the specific face/voice stimuli, so as to minimize taskdependent influences.…”
Section: Discussionmentioning
confidence: 79%
“…The RVF advantage might therefore result from degraded orthographic information transferred from the right hemisphere or, alternatively, from the left-right asymmetry of attention that has been a result of the Western reading style (31). A recent study investigating attentional capture with nonlinguistic stimuli supports the role of differential oscillatory sampling mechanisms for the two hemispheres (32).…”
Section: Split Visual Field Experimentsmentioning
confidence: 92%
“…An alternative explanation is that this activity is a component of an attentional process related to the anticipation of a novel stimulus, and that this anticipation is conducive to processes involved in memory storage (65). It was recently demonstrated that target detection performance fluctuates rhythmically within the theta-band frequency range (66), providing evidence that covert attentional processes, like some exploratory behaviors, are rhythmic in nature and possibly synchronize with oscillatory neural patterns.…”
Section: Discussionmentioning
confidence: 99%